Fundamentals of the development of innovation and investment activities of small and medium-sized businesses in Kazakhstan - A. K. Ibraeva; B. E. Yespenbetova; D. M. Akisheva; L. B. Gabdullina (Путеводитель предпринимателя, 2024)
The article starts by highlighting the significance of small and medium enterprises (SMEs) in the Kazakhstan economy, emphasizing their role as drivers of innovation, job creation, and overall economic development. It discusses the challenges faced by SMEs in accessing finance, technology, and markets, which often hinder their ability to innovate and invest effectively. Moreover, the article delves into the regulatory and institutional frameworks governing SMEs in Kazakhstan, examining the policies and initiatives aimed at fostering a conductive environment for innovation and investment. It explores government support programs, tax incentives, and regulatory reforms designed to stimulate SME growth and entrepreneurship. Furthermore, the paper explores the importance of fostering collaboration and partnerships between SMEs, larger enterprises, research institutions, and government agencies to promote innovation and investment. It discusses the role of industry clusters, innovation hubs, and incubators in facilitating knowledge exchange, networking, and access to resources for SMEs. The article also examines the role of education and skills development in enhancing the innovative capacity of SMEs in Kazakhstan. It highlights the need for targeted training programs, capacity–building initiatives, and entrepreneurship education to equip SMEs with the necessary skills and knowledge to innovate and compete in a globalized economy. Additionally, the article explores the potential of digitalization and technology adoption in driving innovation and investment among Kazakhstan SMEs. It discusses the opportunities presented by digital platforms, e–commerce, and emerging technologies such as artificial intelligence and blockchain in enhancing SME productivity, efficiency, and competitiveness.